Pembuatan Video Profile TK Kartika I-1 Medan Helvetia - Triadi Sya’Dian; Rinanda Purba; Nazarruddin Nazarruddin (Jurnal Kabar Masyarakat, 2023)
This Community Service focuses on creating a video profile for TK Kartika I-1 Medan Helvetia, a pre-school educational institution committed to providing quality education to young children. The aim of this research is to create an engaging and informative video profile that serves as an effective means of introducing the school to the wider community, prospective students, and parents. The research involves collaboration between the research team, the production team, and the school. The research process begins with in-depth interviews with the headmaster, teachers, staff, and parents to gather relevant information about the school's excellence, educational programs, and learning environment at TK Kartika I-1 Medan Helvetia. Additionally, footage is captured at various locations within the school to showcase teaching and learning activities, creative endeavors, and social interactions in a fun-filled ambiance. Diligent editing is carried out to craft the video profile with appropriate audio-visual elements, suitable background music, and engaging narration to enhance its appeal and emotional impact. The result of this endeavor is a comprehensive video profile that showcases the uniqueness and excellence of TK Kartika I-1 Medan Helvetia. The video provides a clear picture of the school's holistic educational approach, positive learning environment, supportive facilities, and the successes of students both inside and outside the classroom. It is anticipated that this video profile will serve as an effective tool in promoting TK Kartika I-1 Medan Helvetia to prospective students and parents and improving the school's image in the eyes of the community. Through broader promotion on social media and other online platforms, this video profile is expected to reach a wider audience of prospective students and families, thereby supporting the school's efforts to shape a generation that is creative, competent, and ready to face future challenges.